Pengaruh Pupuk Kotoran Kambing dan Pupuk NPK Terhadap Pertumbuhan Sawi Pagoda (Brassica narinosa L) dan Derajat Kemasaman Tanah Gambut Pedalaman - Chotimah, Hastin Ernawati Nur Chusnul; Butar Butar, Monica Esmeralda; Saraswati, Dewi; Widyawati, Wahyu; Damanik, Zaffrullah (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This research aims to determine the effect of goat manure and NPK fertilizer on the growth of mustard pagoda and the degree of acidity on inland peat soils. This study used a Factorial Complete Randomized Design consisting of 2 factors and 3 replications. The first factor was goat manure which consisted of 4 levels, namely 0 tons / ha; 25 tons/ha; 35 tons/ha; 45 tons/ha and the second factor was NPK fertilizer which consisted of 3 levels, namely 200 kg/ha; 300 kg/ha; and 400 kg/ha. The results showed that the interaction of goat manure fertilizer and NPK fertilizer did not affect all variables observed, as well as the NPK fertilizer application. However, the application of goat manure fertilizer affected plant height at the age of 2 -3 weeks after planting with a dose of 45 tons / ha with an average of 5.03 cm, the number of leaves in treatment of 35 tons / ha with an average of 6.99 leaves. Treatment of 45 tons / ha showed pH of 5.47 and Treatment of 25 tons / ha gave Al-dd content of 3.57.